From joint to single audits – audit quality differences and auditor pairings / Claus Holm, Frank Thinggaard. - Holm, Claus.
This study analyses audit quality differences between audits by a single big audit firm and joint audits with either one or two big audit firms. We exploit the unique situation in Denmark beginning on 1 January 2005, at which time a long-standing mandatory joint audit system for listed companies was replaced by a voluntary joint audit system. First, we report the results of a survey of Danish CFOs’ views on and their experiences with the choice of single or joint audits and their perceptions of audit quality. Second, based on data from the mandatory joint audit abolition year and the following two years, we test the audit quality differences using abnormal accruals. Most CFOs perceive that audit quality by a single big four audit firm is the same as it is in joint audits with either one or two big four audit firms. The results of our empirical analysis are in line with the perceptions. We find no evidence of audit quality differences between audits made by a single big four firm and those conducted by either of the two combinations of joint audits.